Mediation - Boon or Bane for the Stability and Efficiency of Marriage? - Bianca Rundshagen (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
Using non-cooperative game theory the effects of mediation on the divorce rate and on the utility of the spouses are analysed. Two kinds of mediation are considered: restricted mediation that reduces the costs of divorce and extended mediation that additionally may prevent divorces by demonstrating the potential for Pareto-improvements within marriage to the spouses. It is shown that restricted mediation not only may increase the divorce rate but that also both kinds of mediation are not necessarily welfare improving compared to the reference scenario without mediation.
Keywords: D13; C72; C73; 330